Médias, pédagogie et démocratie - Jean-Pierre Meunier (Centre National d'Enseignement à Distance, 2014)
In the course of the generalized criticism of all forms of power that raged after nineteen-sixty-eight, the media were incriminated in their form, as that they induce a social relation involving a separation between transmitter and receiver, and the unilateral transmission of readable and unambiguous contents . In Belgium, the encounter between militants of some community television (particularly the "Canal emploi" channel of Liège) in search of new educational strategies for the general public, and Geneviève Jacquinot, was the origin of a fruitful search for transforming the form of the media relationship. The theoretical work of Geneviève Jacquinot brought concepts and tools for analysis allowing to curb the audiovisual language in the direction of openness, ambivalence and negotiation of meaning. Following this research, and others of the same kind, one can claim that the issue of meaning production in audiovisual communication has two major aspects: enunciation and cognition. From the standpoint of enunciation, the sense is open when the receivers are placed in a relational configuration opening the possibility of an intersujective debate. From the cognitive point of view, an educational meaning production process occurs when the receptors play an active role in the development of meaning from perceived images and words. The degree of reflexivity involved in this development is an important aspect of this cognitive process. The rhetorical devices which abound in audiovisual productions show a wide variety with respect to this aspect.